THERMAL-NEUTRON INTENSITIES IN SOILS IRRADIATED BY FAST NEUTRONS FROM POINT SOURCES - Shue S.L.; Faw R.E.; Shultis J.K. (My University, 1998)
Thermal-neutron fluences in soil are reported for selected fast-neutron sources, selected soil types, and selected irradiation geometries. Sources include 14 MeV neutrons from accelerators, neutrons from spontaneously fissioning 252Cf, and neutrons produced from alpha-particle interactions in the 241Am/Be source. Soils are of five types, ranging from a dry porous soil to a wet dense soil. Neutron fluences are reported for sources above the soil surface and positioned at selected depths below the soil surface. Methods are demonstrated for incorporating thermal-neutron fluence data into the deconvolution of capture gamma-ray spectral data in the method of assessing soil contamination using prompt gamma-ray neutron activation analysis.
Keywords: THERMAL-NEUTRON INTENSITIES; IRRADIATION GEOMETRY; SOIL TYPE; GAMMA-RAY NEUTRON ACTIVATION ANALYSIS